2001
DOI: 10.1021/jf000999+
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Plant Complex Matrices by Use of Nuclear Magnetic Resonance Spectroscopy:  St. John's Wort Extract

Abstract: The efficiency of two-dimensional homonuclear (1)H--(1)H correlated spectroscopy and two-dimensional reverse heteronuclear shift correlation spectroscopy (i.e., heteronuclear multiple quantum correlation) in characterizing and evaluating the relative content of herbal extract constituents is demonstrated. These experiments are able to fully assign the proton and carbon resonances of all three classes of constituents present in dried commercial extract of St. John's wort, that is, flavonols, phloroglucinols, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 24 publications
2
40
0
1
Order By: Relevance
“…According to Filippini and coworkers [31], although there are several HPLC methods for identification of hypericins and other constituents of H. perforatum [12,16,[20][21][22][32][33][34][35], the recoveries of hypericin, after injection in a C 18 column, is not complete, and therefore the analysis of hypericins by RP-HPLC is problematic. It has also been reported that there are significant differences in the concentrations of hypericin and pseudohypericin as measured by HPLC and UV-vis, with HPLC often giving a lower reading [18].…”
Section: Lc/msmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Filippini and coworkers [31], although there are several HPLC methods for identification of hypericins and other constituents of H. perforatum [12,16,[20][21][22][32][33][34][35], the recoveries of hypericin, after injection in a C 18 column, is not complete, and therefore the analysis of hypericins by RP-HPLC is problematic. It has also been reported that there are significant differences in the concentrations of hypericin and pseudohypericin as measured by HPLC and UV-vis, with HPLC often giving a lower reading [18].…”
Section: Lc/msmentioning
confidence: 99%
“…Antidepressant applications of St. John's wort have become increasingly popular in Europe, especially in countries like Germany where physicians prescribe herbal medicines [11]. H. perforatum medical preparations are prescribed also as dietary supplements [12]. Hypericin (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Occasionally, the different NMR solvents supply complementary data set for PCA model [112]. Except for the optimization of the NMR parameters, 2D NMR is an effective method to solve the overlapped signals [113][114][115]. Yang applied two-dimensional J-resolved NMR spectra and multivariate data analysis techniques for the analysis of commercial ginseng preparations.…”
Section: Nmrmentioning
confidence: 99%
“…Different analytical techniques such as TLC, UV, HPLC, capillary electrophoresis have been employed for analysis of isoflavonoids over the past decades (Drašar and Moravcova 2004;Liu et al 2008;Zhou et al 2009). LC methods with UV detection have questionable specificity for distinguishing compounds of very similar structures as they often exhibit fairly similar UV absorption characteristics (Bilia et al 2001;Cao et al 2008;Dachtler et al 2001;Krause and Galensa 1991;Pietta et al 1991;Qi et al 2006;Rehwald et al 1994;Tian et al 2006;Uchiyama et al 2008;Wu and Thompson 2006;Zhou et al 2008Zhou et al , 2009. Also these methods are time consuming and labour-intensive.…”
Section: Lc-ms/ms Analysis Of Isoflavonoidsmentioning
confidence: 99%